DAMPAK PERILAKU BULLYING TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA REMAJA 11-14 TAHUN - Delvati, Alexandria Dekrasia; Lega, Frans Sales (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
The main question of this study is how the impact of bullying behavior on social emotional development in adolescents aged 11-14 years at the Santo Aloysius Turi Dormitory. This study uses a qualitative approach. Data collection was carried out by interview. There were 12 people who were used as interview sources. The details are 2 dormitory supervisors, 5 students who were victims of bullying and 5 students who were perpetrators of bullying. In addition to interviews, researchers also obtained data through observation and document studies. This study lasted for October-December 2023. The data analysis technique used in this study was a descriptive analysis technique such as (data collection, data reduction, data presentation and drawing conclusions). Based on the results of the study, bullying can be explained as an action that intends to hurt others physically or verbally, degrade someone's mentality, and cause feelings of fear, stress, and anxiety in the victim. This kind of behavior is often carried out by several students at the Santo Aloysius Turi dormitory. The impact of bullying behavior at the Santo Aloysius Turi Dormitory on the social emotional development of several children aged 11-14 years is very significant. On victims of bullying. The impact is that the victim experiences sadness, fear, anger, shame and anxiety, wounds, bruises, feels isolated and has difficulty building healthy social relationships and experiences a decline in academic achievement. While for the perpetrators, the impact of bullying practices on others makes them experience emotional disturbances, rejection from friends, especially victims. Therefore, it is concluded that bullying practices have a negative impact, both on victims and perpetrators of bullying.